Factors Affecting the Branding of Small and Medium Enterprise Products in the Kandy District - Karunaratne, M.M.U.L.; Sathana, V. (University of Sri Jayewardenepura, 2025)
This study aims to identify the factors affecting small and medium enterprise product branding in the Kandy district. The researcher applied a deductive approach since this enables researchers to apply statistical tests to ascertain the relationships between variables. This study used a survey as a research strategy. The sample unit was the owners of small and medium enterprises operating in Kandy, and the study used simple random sampling as the sampling technique. The researcher used the questionnaire to collect primary data, and the questionnaire comprised close-ended questions with a five-point Likert scale. Correlation and regression analysis were used to analyse collected data via questionnaires. The result reveals the significant impacts of Market Size, Brand Associations, Competition, and Product Influences on the branding of small and medium enterprise products in the Kandy district. The most important predictor was product influences, followed by market size and competition. Brand associations had barely any impact on branding. The findings confirmed the correlations among elements of brand associations, product influences, competition, and market size and branding results, and the study adds to the body of information already in use on branding. Therefore, small and medium enterprises must develop strategy frameworks focusing on product quality and distinctiveness from rivals. The study provided important theoretical contributions to the knowledge of branding dynamics, especially in the small and medium enterprise sector and practical consequences that can direct small and medium enterprises to improve their branding initiatives. By concentrating on these elements, small and medium enterprises in the Kandy district must focus on negotiating the complexity of branding in a competitive environment more effectively, thus increasing market success and customer loyalty. Building on these results, future studies can investigate other elements affecting branding and look at their effects in many sectors and environments. Larger and more varied samples reflecting several sectors, areas, and demographic groupings should be included in future research projects; longitudinal studies enable one to monitor changes in results and branding elements across time.
Keywords: Branding; Brand Associations; Competition; Product Influences; Small and Medium Enterprises